2019
DOI: 10.1155/2019/2867372
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ICAM-1 Predicts Poor Survival in High-Grade Serous Ovarian Carcinoma: A Study Based on TCGA and GEO Databases and Tissue Microarray

Abstract: Intercellular cell adhesion molecule-1 (ICAM-1), an important adhesion molecule in the immunoglobulin superfamily, is expressed on many cell types. Recent studies have identified ICAM-1 as a potential oncogene that promotes the development of epithelial ovarian cancer (EOC); it was also found to be associated with poor survival. However, the clinical significance of its expression in high-grade serous ovarian carcinoma (HGSOC) is unclear. Thus, this study aimed to investigate the significance of ICAM-1 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…ARS catalyzes amino acid and transfer RNA (tRNA) binding so that the mRNA sequence is accurately reflected in the protein amino acid sequence. In addition to catalysis, ARS proteins are also involved in inflammation, malignancy, immune system diseases, infections, cardiovascular disease, and nervous system diseases ( 30 , 31 ). Previous data showed that KRS is related to the development of gastric cancer (GC) lung cancer, and melanoma ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…ARS catalyzes amino acid and transfer RNA (tRNA) binding so that the mRNA sequence is accurately reflected in the protein amino acid sequence. In addition to catalysis, ARS proteins are also involved in inflammation, malignancy, immune system diseases, infections, cardiovascular disease, and nervous system diseases ( 30 , 31 ). Previous data showed that KRS is related to the development of gastric cancer (GC) lung cancer, and melanoma ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still few studies on the role of PPL in tumors, and its biological function is not yet clear. This study used public data from TCGA and GEO to conduct a bioinformatic analysis of the correlation between genes and disease ( 23 , 24 ). PPL expression in 31 malignant tumors and the relationship between PPL expression and patient prognosis were analyzed using TCGA.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is however instrumental in providing a novel set of potentially important prognostic markers that may aid survival prognosis and therapy selection in the clinical treatment of HCC. Importantly, it had been reported that expressional levels of ICAM1 serve as a predictor of clinical outcome in several types of cancer including metastatic colorectal cancer (63), indolent non-Hodgkin lymphomas (64), high-grade serous ovarian carcinoma (65) and glioblastoma (66). Within inflamed tissue, ICAM1 was previously found to promote recruitment and survival of immunocytes such as eosinophils and T lymphocytes (67,68).…”
Section: Discussionmentioning
confidence: 99%